2019
DOI: 10.3389/fmicb.2019.02377
|View full text |Cite
|
Sign up to set email alerts
|

Delftibactin-A, a Non-ribosomal Peptide With Broad Antimicrobial Activity

Abstract: The rapid emergence of drug resistant bacteria is occurring worldwide, outpacing the development of new antibiotics. It is known that some of the main sources of antibiotics are the bacteria themselves, many of which are secondary metabolites of Gram positive bacteria. Siderophores, which are secondary metabolites, function as natural chelators (e.g., iron). They are produced and secreted by many bacteria and have been experimented on as “carriers” of several types of antibiotics that pass the cell membrane of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 29 publications
(38 reference statements)
0
26
0
Order By: Relevance
“…A previous study demonstrated that D. acidovorans secreted heat-stable antimicrobial substances that inhibit the growth of S. aureus [23]. Therefore, we assessed the inhibitory activity of D. acidovorans heat-treated CS against S. epidermidis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study demonstrated that D. acidovorans secreted heat-stable antimicrobial substances that inhibit the growth of S. aureus [23]. Therefore, we assessed the inhibitory activity of D. acidovorans heat-treated CS against S. epidermidis.…”
Section: Discussionmentioning
confidence: 99%
“…Delftia acidovorans, a gram-negative bacterium, is detected in the skin of AD patients by microbiome analysis [18][19][20][21][22]. D. acidovorans secretes a compound with antimicrobial activity against S. aureus, Enterococcus faecalis, Acinetobacter baumannii, Klebsiella pneumoniae, and Pseudomonas aeruginosa [23]. Thus, D. acidovorans may affect bacterial growth in the skin microbiome, but the effect of D. acidovorans on the growth of S. epidermidis remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…At the genus level, the composition of Clostridium , Enterococcus , Pseudomonas , Acinetobacter , Desulfovibrio , Delftia , Sphingobium , Brevundimonas , Comamonas , Dysgonomonas , Emticicia , Empedobacter and Sebaldella significantly increased in egg surface (Table S6 ), some of which have also been reported to exhibit antimicrobial activity against various pathogens. For example, many species of genus Pseudomonas have been proved synthesize a variety of compounds with antagonistic activity 28 , 34 ; species of Delftia and Sphingobium produce antimicrobial compounds, which inhibit the growth of some common pathogenic microbes 35 , 36 . The further confrontation culture analysis confirmed the antimicrobial activity of egg surface bacteria against Bt and Bb, and the secondary metabolite analysis demonstrated the potential biosynthesis ability of antimicrobial compounds in these anti-pathogen isolates.…”
Section: Discussionmentioning
confidence: 99%
“…Many species of genus Pseudomonas have been proved synthesize a variety of compounds with antagonistic activity 32,46 . Species of Sphingobium and Delftia are also producing antimicrobial compounds, such as delftibactin A, which inhibit the growth of some common pathogenic microbes 47,48 . These species may play an important role in the defense process of H. oblita larvae against biocontrol agents.…”
Section: Discussionmentioning
confidence: 99%